2007
DOI: 10.4049/jimmunol.179.10.6741
|View full text |Cite
|
Sign up to set email alerts
|

Shaping of the Autoreactive Regulatory T Cell Repertoire by Thymic Cortical Positive Selection

Abstract: The main function of regulatory T lymphocytes is to keep autoimmune responses at bay. Accordingly, it has been firmly established that the repertoire of CD4+CD25+Foxp3+ regulatory T cells (Tregs) is enriched in autospecific cells. Differences in thymic-positive and/or -negative selection may account for selection of the qualitatively distinct regulatory and conventional T cell (Tconv) repertoires. It has previously been shown that precursors for Tregs are less sensitive to negative selection than Tconv precurs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
30
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 65 publications
3
30
0
Order By: Relevance
“…Natural Tregs develop in the thymus, most likely selected via engagement with a strong agonist peptide that would otherwise cause deletion (43). Although some studies have raised the possibility that Treg selection may begin in the cortex (44,45), the majority favor the view that the thymic medulla is the site where Treg precursors mature after contact with intrathymic APCs (2, 4, 46). In this study, we were able to identify B cells within the thymic medulla in close proximity with mTECs and also Tregs, suggesting that thymic B cells were involved in Treg maturation.…”
Section: Discussionmentioning
confidence: 99%
“…Natural Tregs develop in the thymus, most likely selected via engagement with a strong agonist peptide that would otherwise cause deletion (43). Although some studies have raised the possibility that Treg selection may begin in the cortex (44,45), the majority favor the view that the thymic medulla is the site where Treg precursors mature after contact with intrathymic APCs (2, 4, 46). In this study, we were able to identify B cells within the thymic medulla in close proximity with mTECs and also Tregs, suggesting that thymic B cells were involved in Treg maturation.…”
Section: Discussionmentioning
confidence: 99%
“…In this model, tDC gain the capacity to induce expression of Foxp3 in differentiating thymocytes on exposure to thymic stromal lymphopoietin (TSLP) (19). In contradiction to the previously mentioned studies, however, CD25 ϩ and Foxp3 ϩ CD4 ϩ T cells with a suppressive capacity were found in transgenic mice with MHC class II expression restricted to cTEC (20,21). A caveat for these studies, however, was that they did not ascertain whether the commitment of differentiating thymocytes to T R lineage occurred in the cortex; in line with the aforementioned 2-step process of T R differentiation, one can envision a scenario in which TCR stimulation occurs in the cortex, but Foxp3 expression requires medullary production of cytokines.…”
mentioning
confidence: 86%
“…More recently Nedjic et al 9 have shown that thymus cortical cells with a high constitutive level of autophagy contribute to T-cell selection essential for the generation of a self-tolerant T-cell repertoire. The important role of thymus cortical selections, which provides positive selection of conventional T cells, for specific Treg development was also demonstrated by Ribot et al 10 in a single type of MHC molecule experimental model. On these phenomena, we propose that dual types of recognition modes play different roles in the development or differentiation of T cells in the thymus.…”
Section: Adaptive Immunitymentioning
confidence: 64%